Pengaruh Sistem Pengelolaan Organisasi dan Kualitas Pelayanan Internal terhadap Kepuasan Tenaga Kesehatan (Studi pada Tenaga Kesehatan di Puskesmas) - ANASTASIA JESSICA CHRISTI; Albert Surya Wanasida (FEB Universitas Sam Ratulangi Manado, 2022)
This study was conducted to determine the effect of the organizational management system and the quality of internal services on the satisfaction of health workers. The research model was tested empirically on the population of health workers working at the Bali Health Center. Data was collected by convenience sampling with a total of 203 respondents. This study uses the PLS-SEM method to process and analyze the data. The results of this study indicate that the organizational management system has a significant positive effect on the quality of internal services and the quality of internal services has a positive influence on the satisfaction of health workers. The structural model of this study can adequately predict the satisfaction variable of health workers. The results of this study have real implications for Puskesmas in Bali.